Readings in industrial economics (London : Macmillan, 1972)
This book serves as a substitute for vocational course on business studies. Furthermore, it provides an advanced mathematical content for certain contributions made to scientific branch of economics.
Includes index
Includes bibliographical references.
mf 24/10/2019
Loans
Keywords: Rowley, Charles Kershaw; Industrial organization (Economic theory); Externalities (Economics); Industrial policy